Geochronology, geochemistry and geodynamic implications of the Late Mesozoic volcanic rocks in the southern Great Xing'an Mountains, NE China. (1st December 2015) - Yang, Wu-Bin; Niu, He-Cai; Cheng, Li-Ren; Shan, Qiang; Li, Ning-Bo
Highlights: The volcanic rocks have ages of Late Mesozoic, and are dominantly in Early Cretaceous. The intermediate and felsic volcanic rocks were derived from mantle and crust, respectively. The large-scale igneous event was induced by the transformation of tectonic regime. Abstract: Large-scale Mesozoic volcanisms in the Great Xing'an Mountains (GXM), northeastern (NE) China, are being extensively interested recently. However, the petrogenesis and geodynamic implications of these volcanic rocks are still on controversy. In this study, geochronology and geochemistry of the intermediate and felsic volcanic rocks of Late Mesozoic from the southern GXM was investigated. Zircon U–Pb geochronology yields 206 Pb/ 238 U ages ranging from 154.3 ± 1.7 Ma to 127.0 ± 2.4 Ma for the eight selected volcanic rocks, where the major period of the Mesozoic volcanisms is constrained during the Early Cretaceous. The presented volcanic rocks are andesite–trachydacite–rhyolite and show calc-alkaline to shoshonitic features. They have elevated incompatible trace element concentrations and significantly negative Nb–Ta–Ti and positive Pb anomalies, which display characteristics of typical subduction-related magmas rather than within-plate magmatic signature. Sr–Nd isotopic data indicate that their magma sources were mixed with proportions of old crustal components. Geochemical features, therefore, indicate that the intermediate and felsic shoshonitic magma was plausibly derived from partial melting of the subduction-modified lithospheric mantle and thickened lower crust, respectively, induced by delamination and/or asthenosphere upwelling in extensional setting. Combined with the tectonic evolution of the Great Xing'an area, we propose a hypothesis that the large-scale Mesozoic volcanisms in NE China were controlled by the transition of regional stress from southward to westward, which are induced by the changes of tectonic regimes from the previous Mongol–Okhotsk subduction to the succeeding paleo-Pacific subduction during Late Mesozoic.